Perfil epidemiológico e de saúde de crianças e adolescentes com Transtorno do Espectro Autista de uma associação do interior do Amazonas - Costa, Chris Stéphanie Batista da (Brasil, 2025)
Objective: To characterize the health and epidemiological profile of children and adolescents with ASD from an Association in the interior of Amazonas. Methods: Methods: Descriptive cross-sectional study, carried out in the pediatric physiotherapy sector of the Institute of Health and Biotechnology - ISB of the Federal University of Amazonas - UFAM, with children and adolescents with ASD and their parents or guardians. The research included participants aged between 1 and 14 years, diagnosed or suspected of having ASD, members of the Association of United Parents for Autistic People of Coari (PUPAC) and involved in the FisioTEA extension project of the ISB/UFAM. Data were collected between October and November 2024, using project evaluation forms and were analyzed by descriptive statistics in the Jamovi software. The collection followed the ethical precepts of Resolution 466/2012, with approval by the Research Ethics Committee. Results: In the prenatal period, 28 (70%) cases were associated with maternal infections, and 26 (65%) of the mothers had an adequate number of prenatal care visits. Regarding perinatal factors, 9 (22,5%) were born preterm; 13 (32,5%) were delivered via vaginal birth, while 23 (57,5%) underwent cesarean delivery. Additionally, 27,5% of mothers reported that their children and adolescents experienced fetal distress, injury or trauma, breathing difficulties at birth, and neonatal jaundice. Conclusion: The study identified sociodemographic, prenatal, perinatal, and postnatal characteristics that may serve as risk factors for ASD. The research findings highlight the need for ongoing investigation and reveal that the implementation of preventive practices during pregnancy and perinatal care is essential to reducing the impact of ASD and improving the quality of life for children. Further exploration of these factors can enhance healthcare services and inform the development of effective strategies, particularly in remote regions.